Resveratrol Metabolites Are Able to Reduce Steatosis in Cultured Hepatocytes - Trepiana, Jenifer (Pharmaceuticals (Basel), 2020)
Steatosis is characterized primarily by excessive lipid accumulation in the form of triglycerides in the liver. Although resveratrol shows a low bioavailability, it has significant positive effects on steatosis. The aim of this study was to analyze whether some phase II and microbial resveratrol metabolites (trans-resveratrol-4′-O-glucuronide (R-4G); trans-resveratrol-3-O-glucuronide (R-3G); trans-resveratrol-3-O-sulfate (R-S) and dihydro-resveratrol (DH-R) were effective in reducing hepatocyte fat accumulation. An in vitro model mimicking the hepatocyte situation in fatty liver was developed by incubating mouse AML12 hepatocytes with palmitic acid (PA). For cell treatments, hepatocytes were incubated with 1, 10, or 25 µM resveratrol or its metabolites. Triglycerides and cell viability were assessed using commercial kits. Protein expression of enzymes and transporters involved in triglyceride metabolism were analyzed by western blot. We show for the first time that resveratrol and all the tested metabolites, at 1 µM, partially prevented lipid accumulation induced by the saturated fatty acid PA in AML12 hepatocytes. This effect was mainly due to the inhibition of de novo lipogenesis. This demonstrates that the low bioavailability of resveratrol is not as big a problem as it was thought to be, because resveratrol metabolites contribute to the delipidating effects of the parent compound.